Influences causing variation in butter-fat production - Baird, Wallace W. (My University, 1904)
Introduction: It is a well known fact that changes in the weather, feed, care and treatment of the cow affects the production of butter-fat also, that the test and the amount of milk varies greatly from milking to milking with a single cow, while the average test from a herd varies but little. Where a great deal of milk is produced by a cow the test is apt to be low, and where there is little milk produced the test is usually high. The question of condi ti ons which affect the producti on of butter-fat is a complicated one in as much as one condi ti on may counteract the effect of another --for instance, good shelter and a little extra care will counteract the effect of severe weather, while rough handling will reduce the advantages obtained by good feeding. The reas on for mak ing this exper iment was that no experiment of the kind which covers a long period is on record. Twelve cows were selected from the College dairy herd --six of them thorough-breds, Jerseys, Holsteins and Ayrshires, and six of them grades and scrubs. The milk was carefully weighed after each milking and samples taken and tested. The time covered was one hundred thirty-seven days beginning with the 11th of December and ending the 25th of April. Five of the scrub cows were dropped during February and March and were replaced by four others, but the thorough-breds and one scrub were tested the whole time.
Citation: Baird, Wallace W. Influences causing variation in butter-fat production. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Butter-Fat; Food Production; Dairy Products; Factors Affecting Production; Theses